APPLICATION OF RESPONSE SPECTRUM ANALYSIS (RSA) IN THE DESIGN OF HIGH-RISE BUILDING WITH VISCOELASTIC DAMPER (VED) - Pramitari Wima Devi Sagung Istri; Prasanti W. Sarli; Andri Setiawan; Yuni Azhari; Angga Adiawan; Andri Saputra Gunawan (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2026)
Earthquake-resistant structures using dampers have begun to be implemented in Indonesia. Structures equipped with dampers can reduce plastic deformation in primary structural elements, inter-story drift, and floor acceleration. According to SNI 1726:2019 Article 13, the seismic design analysis of structures with damping systems may employ nonlinear time history analysis (NLTHA) or alternative procedures such as response spectrum analysis (RSA) and equivalent lateral force (ELF). However, NLTHA is computationally inefficient and requires considerably longer processing time compared to alternative procedures. The RSA procedure also stipulates that dampers may be used solely to satisfy inter-story drift requirements per SNI 1726:2019, so that bare frame structures can be analysed conventionally to meet the strength requirements of SNI 2847:2019. The novelty of this research lies in applying the RSA method as a computationally efficient alternative to NLTHA for the analysis and design of structures with viscoelastic dampers (VED), which is not yet widely practiced by engineers in Indonesia. In this study, the structure was modelled with VED and analysed using RSA through iterative stages: viscous damping iteration (βvm), iteration at the DBE earthquake level to satisfy the minimum base shear V and βmd ≤ 35%, and iteration at the MCER earthquake level to satisfy story drift and story displacement limits. Using the RSA method, 12 dampers per direction (24 per floor) were installed, satisfying the RSA minimum requirement of 2 dampers per direction and 4 dampers per floor. Based on the analysis, the minimum base shear (Vmin) was 0.9085V. It is concluded that the alternative RSA procedure can be applied and satisfies the requirements of SNI 1726:2019 for damping systems.